Analisis Konsep Adat Istiadat Yahudi dan Pendidikan Multikultural dalam Pembelajaran Pluralisme - Noviyanti Herlina; Fransiska Hasugian; Darwin Sibarani; Yehezkiel Telaumbanua; Wilson Simanjuntak (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This research aims to analyze the concept of Jewish customs in the context of multicultural education and explore its integration in pluralism learning. Using a qualitative approach, this research examines how understanding Jewish customs can enrich the educational curriculum and build attitudes of tolerance among students. The research results show that the integration of material about Jews, through a thematic approach, allows students to link the values ​​taught with contemporary social issues, so that learning becomes more relevant and meaningful. This research also emphasizes the importance of the teacher's role as a facilitator in creating an inclusive learning environment. Thus, it is hoped that this research can contribute to the development of a more inclusive and relevant curriculum, as well as forming a generation that respects diversity and is able to contribute positively to a plural society.